The Impact of Information and Communication Technology (ICT) Development on Economic Growth in Sudan: An Application of ARDL Bounds Testing Approach - Khater, Ahmed Mohammed; Allah, Babiker Abdelrazig Wagee (Archives of Business Research, 2017)
The aim of this study to investigates the impact of Information and Communication Technology (ICT) development on economic growth in Sudan. Annually data over the period (1980-2014) of economic growth (GDP), Information and Communication Technology ICT (Fixed phone line, mobile cellular and internet subscribers per 100 inhabitants) and macroeconomic factor (Gross fixed capital formation and labor force) were modeled Using the bound testing approach to co integration and Error Correction Model (ECM), developed within an Autoregressive Distributed Lag (ARDL) framework, the study investigates whether a long-run relationship exists among the variables. From the results, it is evident that there is an existence of a long run relationship between ICT and economic growth. The short run dynamic model also reveals that the speed of convergence to equilibrium is moderate implying that there is a short run relationship between ICT and economic growth.